Alteration of Occlusal Plane in Orthognathic Surgery: Clinical Features to Help Treatment Planning on Class III Patients - Daniel Amaral Alves Marlière; Tony Eduardo Costa; Saulo de Matos Barbosa; Rodrigo Alvitos Pereira; Henrique Duque de Miranda Chaves Netto (Case Reports in Dentistry)
Dentofacial deformities (DFD) presenting mainly as Class III malocclusions that require orthognathic surgery as a part of definitive treatment. Class III patients can have obvious signs such as increasing the chin projection and chin throat length, nasolabial folds, reverse overjet, and lack of upper lip support. However, Class III patients can present different facial patterns depending on the angulation of occlusal plane (OP), and only bite correction does not always lead to the improvement of the facial esthetic. We described two Class III patients with different clinical features and inclination of OP and had undergone different treatment planning based on 6 clinical features: (I) facial type; (II) upper incisor display at rest; (III) dental and gingival display on smile; (IV) soft tissue support; (V) chin projection; and (VI) lower lip projection. These patients were submitted to orthognathic surgery with different treatment plannings: a clockwise rotation and counterclockwise rotation of OP according to their facial features. The clinical features and OP inclination helped to define treatment planning by clockwise and counterclockwise rotations of the maxillomandibular complex, and two patients undergone to bimaxillary orthognathic surgery showed harmonic outcomes and stables after 2 years of follow-up.